HUBUNGAN KARAKTERISTIK MASYARAKAT DENGAN KEJADIAN COVID 19 DI DESA PAYUNG KECAMATAN WELERI - Sri Hesthi Sonyorini; Sulastri Sulastri (LPPM STIKES Muhammadiyah Kendal, 2021)
At this time there is a health problem that is in the spotlight and attention of the world, namely the Covid-19 disease. This disease is caused by a virus called Corona Virus Disease – 19 or more popularly known as Covid-19. In response to this, the government has issued a policy or regulation to prevent the increase in the number of cases, namely in the form of a health protocol for handling Covid-19. The government has issued health protocols for handling Covid-19, including health protocols, borders, communications, education areas, and public and transportation areas, including policies in the form of implementing Large-Scale Social Restrictions (PSBB) in several areas in Indonesia. This study aims to determine the relationship between community characteristics and the incidence of covid 19 in Payung Village, Weleri District. Research design is descriptive correlation with sampling technique using simple random sampling with a sample of 58 respondents. Statistical analysis using chi square. From the results of the study, it was found that there was a relationship between age, gender, education and occupation with the incidence of Covid-19 in Payung Village, Weleri District with a p value <0.05.